APPLICATION AND DEVELOPMENT OF ISLAMIC FINANCIAL INSTRUMENTS IN COMMERCIAL BANKS (European Journal of Economics, Finance and Business Development, 2025)
The article shows how Islamic financial structure is applied by commercial banks in Uzbekistan and analyzes the development of assets worldwide.